Urban lynches. Popular executions in times of citizen security - Santillán, Alfredo (2008)
The article presents results of a short-term research on lynching and lynching attempts happened in Quito during 2007. The analysis about these facts has to do with the relationships between executing acts and the brand-new “citizen security” paradigm, whose practices and discourse have proliferated in a dissimilar way promoting “community participation” on security work.  Contradictions  in  this  paradigm,  along  with  an  incresing  perception  of  insecurity  and helplessness, are components that suit lynching as a collective violence form, whose character is punitive and punishing.